2019
DOI: 10.1007/s11831-019-09352-w
|View full text |Cite
|
Sign up to set email alerts
|

Fifty Shades of Brain: A Review on the Mechanical Testing and Modeling of Brain Tissue

Abstract: Brain tissue is not only one of the most important but also the most complex and compliant tissue in the human body. While long underestimated, increasing evidence confirms that mechanics plays a critical role in modulating brain function and dysfunction. Computational simulations-based on the field equations of nonlinear continuum mechanics-can provide important insights into the underlying mechanisms of brain injury and disease that go beyond the possibilities of traditional diagnostic tools. Realistic numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
309
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 311 publications
(322 citation statements)
references
References 172 publications
12
309
1
Order By: Relevance
“…There is no global agreement on the effect of prolonged storage of brain tissue on mechanical properties, with some authors concluding there is minimal effect up until 5 days post-mortem (Budday et al, 2015 ), while others conclude that as short as 6 h of storage can affect the properties (Garo et al, 2007 ). As concluded by Budday et al ( 2019 ) in their review paper of brain tissue, we have considered that, provided the tissue is kept sufficiently hydrated, the degeneration process of post-mortem tissues is negligible. Similarly, it has been previously reported that increasing the temperature from ambient conditions to physiological conditions (37°C) significantly reduces the stiffness of brain tissue (Pogoda et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is no global agreement on the effect of prolonged storage of brain tissue on mechanical properties, with some authors concluding there is minimal effect up until 5 days post-mortem (Budday et al, 2015 ), while others conclude that as short as 6 h of storage can affect the properties (Garo et al, 2007 ). As concluded by Budday et al ( 2019 ) in their review paper of brain tissue, we have considered that, provided the tissue is kept sufficiently hydrated, the degeneration process of post-mortem tissues is negligible. Similarly, it has been previously reported that increasing the temperature from ambient conditions to physiological conditions (37°C) significantly reduces the stiffness of brain tissue (Pogoda et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…We adapted the directed differentiation of human oligodendrocytes from hiPSCs that we previously developed (Douvaras et al, 2014;Douvaras and Fossati, 2015) to a well-established system of polyacrylamide (PAAm) hydrogels (Tse and Engler, 2010;Pelham and Wang, 1997;Moshayedi et al, 2010;Jagielska et al, 2012) functionalized to facilitate cell adhesion to their surface ( Figure 1A). The hydrogels mimic a range of stiffness described by Young's elastic modulus E (of magnitude 0.1-70 kPa) that approximates and exceeds the stiffness of the human CNS environment (Murphy et al, 2016;Budday et al, 2017Budday et al, , 2019McIlvain et al, 2018;Urbanski et al, 2019; Figures 1B,C). In other words, these hydrogels span the range of physiological and pathological CNS stiffness.…”
Section: Human Oligodendrocytes Exhibit Mechanosensitive Migration Inmentioning
confidence: 95%
“…Some experimental studies suggest that brain tissue is mechanically isotropic, e.g., Budday et al (2017), while others suggest brain tissue show significant directional trends, e.g., Prange and Margulies (2002), Feng et al (2017). More discussion on the controversies can be found in a review study by Budday et al (2019). Nevertheless, both isotropic and anisotropic models are being used in head models for studying TBIs; see review studies (Giudice et al 2019;Madhukar and Ostoja-Starzewski 2019).…”
Section: Materials Modeling Choice For the Brain Falx Tentorium Durmentioning
confidence: 99%